2017
DOI: 10.1089/aid.2016.0321
|View full text |Cite
|
Sign up to set email alerts
|

Complex Subtype Diversity of HIV-1 Among Drug Users in Major Kenyan Cities

Abstract: Drug users are increasingly recognized as a key population driving human immunodeficiency virus (HIV) spread in sub-Saharan Africa. To determine HIV-1 subtypes circulating in this population group and explore possible geographic differences, we analyzed HIV-1 sequences among drug users from Nairobi, Mombasa, and Kisumu in Kenya. We sequenced gag and env from 55 drug users. Subtype analysis from 220 gag clonal sequences from 54 of 55 participants (median = 4/participant) showed that 44.4% were A, 16.7% were C, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
5
7
0
Order By: Relevance
“…The present study detected higher prevalence of subtype A1 (78.4%) followed by AG 16.2%), A1/C (2.7%) and A1/G/AE (2.7%) infection among injection drug users. This is partly consistent with previous study reporting higher prevalence of envelope-gene subtype A1 and the remainder being AD, C and complex subtypes in that order, among injection drug users in Nairobi city (8). Studies assessing in vitro HIV subtype replication capacity found that A has a higher replication fitness hence increased transmission compared to other subtypes (23,24), may explain the expansion of subtype A in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…The present study detected higher prevalence of subtype A1 (78.4%) followed by AG 16.2%), A1/C (2.7%) and A1/G/AE (2.7%) infection among injection drug users. This is partly consistent with previous study reporting higher prevalence of envelope-gene subtype A1 and the remainder being AD, C and complex subtypes in that order, among injection drug users in Nairobi city (8). Studies assessing in vitro HIV subtype replication capacity found that A has a higher replication fitness hence increased transmission compared to other subtypes (23,24), may explain the expansion of subtype A in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…At least two of these studies [17,20] tested many subtype samples collected from around the world including Africa. These studies include the predominant HIV subtypes seen in Kenya such as subtype A, D, C, G and recombinants [21,22,36,37]. The good agreement seen between Aptima VL results and Abbott RT seen in this study also suggest that subtype quantification of Aptima is equivalent to that of Abbott RT for the HIV subtypes prevalent in Kenya.…”
Section: Plos Onesupporting
confidence: 70%
“…Several publications demonstrate equivalent performance of the Aptima Assay with other commercially available assays, but most of these were conducted by testing plasma specimens from HIV patients in Europe and the United States [10][11][12][13][14][15][16][17][18][19][20]. Unlike the United States and Europe where the predominant HIV subtype is subtype B, Africa has the greatest genetic diversity of HIV-1 with Kenya having high level of infection with recombinants, subtype A, C and D [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…HIV gag-protease was amplified by bulk PCR using previously described protocols (19). Single genome amplification (SGA) of gag was performed, as described previously (20), by serial dilution of cDNA to determine a dilution where ≤30% of wells were positive for amplification. The ABI Prism Big Dye Termination V 3.1 cycling sequencing kit (Applied Biosystems, Waltham, Massachussetts) was used to Sanger sequence bulk PCR products and single genome amplicons using previously published primers (19,20).…”
Section: Gag Amplification and Sequencing From Plasma Ln Mononuclear ...mentioning
confidence: 99%